The impact of e-Wom on customer purchasing decision among UiTM Samarahan degree students / Ahmad Fikri Roslan - Roslan, Ahmad Fikri (2015)
The purpose of the study is to identify what are the factors of electronic word of mouth (e-WOM) impacting the customer purchase decision among UiTM Samarahan students. The determinants or factor of e-WOM among degree student of UiTM Samarahan were discussed in this research and also about online opinion, e-WOM credibility and e- WOM volumes. The objective of this research is to identify the relationship between online opinion with the customer purchase decision among student of UiTM Samarahan, to identify the relationship between e-WOM credibility with the customer purchase decision among students of UiTM Samarahan, to identify the relationship between e-WOM volumes with the customer purchase decision among student of UiTM Samarahan, to identify most influential factors of e-WOM that impacting the customer purchase decision among UiTM Samarahan students. The survey involves of 150 respondents from UiTM Samarahan degree students. Data obtained using primary and secondary data. The data was analyzed using SPSS software to get Frequency, Reliability, Correlation and Regression. The results are all independent variables have a relationship to the customer purchase decision among UiTM Samarahan degree students.